2017
DOI: 10.1186/s12877-017-0649-3
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure at age 60–65 versus age 70–75 and vascular dementia: a population based observational study

Abstract: BackgroundVascular dementia (VaD) is the second most common form of dementia. However, there were mixed evidences about the association between blood pressure (BP) and risk of VaD in midlife and late life and limited evidence on the association between pulse pressure and VaD.MethodsThis is a population-based observational study. 265,897 individuals with at least one BP measurement between the ages of 60 to 65 years and 211,116 individuals with at least one BP measurement between the ages of 70 to 75 years were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…Some studies reported that high blood pressure at midlife (age 40–64 years) is associated with an increased risk of late-life dementia ( 17 , 18 ). Currently, there is no consensus on the association between blood pressure and dementia in those aged 65 years and above ( 29 , 30 ). On the contrary, some studies ( 16 , 31 ) suggest that hypotension is associated with greater dementia risk in older age, primarily owing to concerns that aggressive blood pressure reduction could cause hypoperfusion of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that high blood pressure at midlife (age 40–64 years) is associated with an increased risk of late-life dementia ( 17 , 18 ). Currently, there is no consensus on the association between blood pressure and dementia in those aged 65 years and above ( 29 , 30 ). On the contrary, some studies ( 16 , 31 ) suggest that hypotension is associated with greater dementia risk in older age, primarily owing to concerns that aggressive blood pressure reduction could cause hypoperfusion of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Similar but even weaker associations were seen between WMH and BP at the age of 73 years ( Aribisala et al, 2014 ). In addition, Peng et al (2017) reported no association between BP levels nor peripheral PP at the age of 70–75 years and the incidence of vascular dementia.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, the association between high BP in middle age (age 40–64 years) and increased risk for vascular dementia is well established ( Kennelly et al, 2009 ; Launer et al, 2010 ; Ninomiya et al, 2011 ). However, studies looking at these associations at an older age are sparse and there is no consensus on the association between BP and dementia in individuals aged 75 and above ( Peng et al, 2017 ). In addition, information about the impact of BP and arterial stiffness measures on white matter integrity in people over 75 years old is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanisms linking PWD and hypertension need to be investigated. Indeed, hypertension is known to lead to endothelial alterations and microvascular dysfunction, increasing inflammation and oxidative stress, 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 which may underlie structural and electro‐mechanical alterations in the heart.…”
Section: Discussionmentioning
confidence: 99%